Making sense of an unknown terrain: how parents understand self-harm in young people - Hughes, N; Locock, L; Simkin, S; Stewart, A; Ferrey, A; Gunnell, D; Kapur, N; Hawton, K (SAGE Publications, 2015)
Self-harm is common in young people, and can have profound effects on parents and other family members. We conducted narrative interviews with 41 parents and other family members of 38 young people, aged up to 25, who had self-harmed. Most of the participants were parents but included one sibling and one spouse. This article reports experiences of the parent participants. A cross-case thematic analysis showed that most participants were bewildered by self-harm. The disruption to their worldview brought about by self-harm prompted many to undergo a process of “sense-making”—by ruminative introspection, looking for information, and building a new way of seeing—to understand and come to terms with self-harm. Most participants appeared to have been successful in making sense of self-harm, though not without considerable effort and emotional struggle. Our findings provide grounds for a deeper socio-cultural understanding of the impact of self-harm on parents.